2006
DOI: 10.1152/jn.00927.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex–Projecting Glutamatergic Thalamic Paraventricular Nucleus-Excited by Hypocretin: A Feedforward Circuit That May Enhance Cognitive Arousal

Abstract: The paraventricular thalamic nucleus (PVT) receives one of the most dense innervations by hypothalamic hypocretin/orexin (Hcrt) neurons, which play important roles in sleep-wakefulness, attention, and autonomic function. The PVT projects to several loci, including the medial prefrontal cortex (mPFC), a cortical region involved in associative function and attention. To study the effect of Hcrt on excitatory PVT neurons that project to the mPFC, we used a new line of transgenic mice expressing green fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 76 publications
5
95
0
Order By: Relevance
“…2 F) and with previous reports of vGluT2 expression. Other positive cells were found in the cortex, amygdala, and thalamus (Huang et al, 2006). In contrast, neurons that were known to express vGluT1 and not vGluT2, for instance the CA3 pyramidal cells of the hippocampus (Fremeau et al, 2001), were negative for GFP in this transgenic mouse.…”
Section: Expression Of Gfp With Vglut2 Promoter In Neurons Of the Vmhmentioning
confidence: 73%
See 1 more Smart Citation
“…2 F) and with previous reports of vGluT2 expression. Other positive cells were found in the cortex, amygdala, and thalamus (Huang et al, 2006). In contrast, neurons that were known to express vGluT1 and not vGluT2, for instance the CA3 pyramidal cells of the hippocampus (Fremeau et al, 2001), were negative for GFP in this transgenic mouse.…”
Section: Expression Of Gfp With Vglut2 Promoter In Neurons Of the Vmhmentioning
confidence: 73%
“…In these vGluT2 mice, GFP is selectively expressed in glutamatergic vGluT2-expresssing neurons but not in other cells. The sequence of the vGluT2 promoter construct used to drive GFP expression in these transgenic mice has been described previously (Huang et al, 2006). Briefly, the vGluT2 promoter, 1.8 kb upstream from the vGluT2 sequence, was used to drive GFP expression.…”
Section: Methodsmentioning
confidence: 99%
“…In any case, the rapid postnatal dendritic growth (Bicknell Jr and Beal 1984) and the predominance of tonic action potential discharge in young rat SDH neurons (Baccei and Fitzgerald 2005;) suggest that adult cell classification systems may be inappropriate. This issue could be addressed using selective green fluorescent protein-labeled transgenic mice (Daniele and MacDermott 2009;Huang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the enhanced mEPSC rate could reflect the conversion of "silent" ("NMDAR only") synapses, which are present in the SDH during the first two postnatal weeks (Baba et al 2000;Bardoni et al 1998;Li and Zhuo 1998), to functional connections via the insertion of AMPARs into the postsynaptic membrane (Isaac et al 1997). However, the evidence suggests this is unlikely to explain the elevated mEPSC frequency after neonatal incision.…”
Section: Discussionmentioning
confidence: 99%
“…The processes that are regulated by the paraventricular thalamic nucleus, such as arousal and attention, as well as in the effects of stress on body temperature and energy balance (van der Werf et al, 2002;Kirouac et al, 2005;Bhatnagar and Dallman, 1999;Huang et al, 2006), have not been reported to be affected by 5-HT 7 receptor activation.…”
Section: Discussionmentioning
confidence: 99%